Disonansi Perilaku Berpikir Pascainternalisasi Konsep Jender Ditinjau dari Dimensi Kesamaan, Kesepadanan, dan Perbedaan di Pondok Pesantren - Amat Mukhadis (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The study was intended to explore and describe the dissonance level of thinking behaviors in the daily life of traditional Muslem schools after the internalization of gender concept. The sample was purposively taken, comprising 4 religious leaders, 24 Islamic teachers, and 57 students. The data were collected using questionnaire, interview, and observation. The results show that the dissonance level of thinking behaviors among the Islamic teachers was relatively high, whereas that of the three groups ranged from accepting to hesitating. This was assumed to have been caused by the low level of understandings of gender concept.